Political discussion networks and political engagement among voters of color - Carison, T.N, Abrajano, M. and Bedotla, L.G. (Political Research Quarterly)
Despite a large and growing literature documenting the powerful and positive role that political discussion networks exert on the political behavior among whites, we know little about how political discussion networks affect political behavior among voters of color. To fill this void in the existing literature, we conducted an original survey in California to gather information on a diverse group of registered voters$1 (Bpolitical discussion networks and political engagement. The social positioning of ethnoracial groups in society, we contend, will affect how network characteristics explain their levels of political engagement. Our results support this contention. While we find that network characteristics, including network size, partisan homogeneity, and discussion frequency are positively associated with validated voter turnout and nonelectoral political participation, the effects are not uniform across black, Latino, Asian American, and white respondents. This is the first study that examines the relationship between political discussion network characteristics and political engagement among voters of color. Our analysis demonstrates that the opportunities for political integration and engagement offered by political discussion networks are not afforded equally across the U.S. electorate, which has important implications for broader patterns of engagement.- Reproduced s
Keywords: Political discussion, Networks, Race, Ethnicity, Political participation